RESPONSE OF SEED GERMINATION AND GROWTH OF Nepenthes gymnamphora Nees IN VITRO TO THE CONCENTRATION OF MS MINERAL SALT, PEPTONE AND THIDIAZURON - Nurchayati, Yulita (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Nepenthes gymnamphora Nees is a Java's rare endemic species. Ex-situ conservation of this endangered species can be done through in vitro culture technique. The aims of this study were to determine (1) the mineral salt concentration of MS basal media and addition of peptone (P) on N. gymnamphora seed germination and seedling emergence and (2) the effects of TDZ in ½MS medium on seedling growth. Seeds were surface sterilized and cultured on four media formulations (½MS, MS, ½MS+P, MS+P) for 8 weeks. In the second experiment, ten-week-old seedlings, 0,25 cm in length were cultured on ½MS supplemented with 0, 0,5, 1,0, or 1,5 mg/L TDZ. Seedling growth was recorded at 8 weeks of culture. Results of this experiment showed that ½MS was the best medium for N. gymnamphora seed germination as indicated by the highest percentage of germination, the tallest seedling, and the fastest seedling emergence. Moreover, the best growth of N. gymnamphora was found on ½MS without TDZ.